Analytical errors in the laboratory of a general hospital of the Thai Red Cross Society: A 3-year experience - Trakulkaseamsiri, Srivilai; Chumchujan, Kittipong (Journal of Associated Medical Sciences, 2025)
Background:Laboratory test results are critical to clinical decision-making, including patient screening, diagnosis, treatment planning, and monitoring therapeutic responses. Therefore, laboratory errors can significantly impact patient care and outcomes. Objectives:To identify and quantify the types and frequencies of errors in the total testing process of the medical laboratory department, with the goal of reducing preventable errors and improving overall quality. Materials and Methods:This retrospective descriptive study analyzed error records, incident reports and nonconformities from January 2021, to December, 2023. Errors were categorized by testing phase: pre-analytical, analytical and post-analytical. Specimen sources were classified as outpatient, inpatient, or external (outside hospital). Data were summarized using descriptive statistics, including frequencies, percentages and Six Sigma performance scale values. Results:A total of 2,261,729 specimens were received during the study period. The overall error rate was 0.197% (4,460 errors). Error rates by phase were 0.116% for pre-analytical, 0.077% for analytical, and 0.004% for postanalytical. Six Sigma performance scores were 4.60 (pre-analytical), 4.70 (analytical), and 5.50 (post-analytical), all within acceptable quality thresholds (>4.15, >3.85 and >4.80, respectively). The most common pre-analytical error was clotted samples (1,233 cases). Analytical errors were dominated by unacceptable internal quality control results (1,088 cases). The most frequent post-analytical error was excessive turnaround time (54 cases). Pre-analytical errors occurred most frequently in inpatient specimens (76.90%), with clotted samples accounting for 41.49% of those cases. Six Sigma values by specimen source were 4.20 for inpatients, 4.90 for outpatients and 4.90 for external sources. Conclusion: Most laboratory errors occurred in the pre-analytical phase, primarily due to specimen collection issues related to quality and volume, particularly in the inpatient setting. Targeted preventative measures-especially in pre-analytical processes-are essential to minimize errors and improve patient safety. Analytical errors were primarily due to unacceptable IQC, EQA. For quality control improvement, training program laboratory staff on quality control, sigma metrics, risk assessment and quality goal index (QGI), including selection and application of Westgard’s rules, is important. The integration of sigma metrics with QGI, risk management and systematic quality control can enhance laboratory performance and reliability of analytical results.enhance laboratory performance and reliability of analytical results.